Characterization of a 4.1 Mb inversion harboring the stripe rust resistance gene YR86 on wheat chromosome 2AL - Qiang Cao; Zhanwang Zhu; Dengan Xu; Jianhui Wu; Xiaowan Xu; Yan Dong; Yingjie Bian; Fugong Ding; Dehui Zhao; Yang Tu; Ling Wu; Dejun Han; et al. (Elsevier, 2024)
Wheat cultivar Zhongmai 895 was earlier found to carry YR86 in an 11.6 Mb recombination-suppressed region on chromosome 2AL when crossed with Yangmai 16. To fine-map the YR86 locus, we developed two large F2 populations from crosses Emai 580/Zhongmai 895 and Avocet S/Zhongmai 895. Remarkably, both populations exhibited suppressed recombination in the same 2AL region. Collinearity analysis across Chinese Spring, Aikang 58, and 10+ wheat genomes revealed a 4.1 Mb chromosomal inversion spanning 708.5–712.6 Mb in the Chinese Spring reference genome. Molecular markers were developed in the breakpoint and were used to assess a wheat cultivar panel, revealing that Chinese Spring, Zhongmai 895, and Jimai 22 shared a common sequence named InvCS, whereas Aikang 58, Yangmai 16, Emai 580, and Avocet S shared the sequence named InvAK58. The inverted configuration explained the suppressed recombination observed in all three bi-parental populations. Normal recombination was observed in a Jimai 22/Zhongmai 895 F2 population, facilitating mapping of YR86 to a genetic interval of 0.15 cM corresponding to 710.27–712.56 Mb falling within the inverted region. Thirty-three high-confidence genes were annotated in the interval using the Chinese Spring reference genome, with six identified as potential candidates for YR86 based on genome and transcriptome analyses. These results will accelerate map-based cloning of YR86 and its deployment in wheat breeding.